Orahua: the Elitism of indigenous social institutions and deliberations in South Nias, Indonesia - Sastri Sunarti; Ninawati Syahrul; Erli Yetti; Suryami; Agus Iswanto; Refisrul; Sumarno; Aam Masduki (Cogent Social Sciences, 2024)
Amid societal developments that have adopted modern democratic practices, the tradition of customary deliberations continues to be used to manage daily life. Local social institutions that operate based on the ideologies of local democracy passed down for generations can still be found in a village in the South Nias (Sumatra). This study focuses on how powerful Orahua is as a local social institution in South Nias. To answer this question, qualitative research was conducted on the practices of Orahua in the village of Hilinawalo Batusalawa, South Nias. Data were collected through observation and in-depth interviews with supporters of Orahua, such as Si Ulu and Si Ila (descendants of a king and nobility, respectively), as well as other individuals in the research location. The results show that the community has succeeded in adapting the practices of Orahua from a forum for deliberation on customary law to a forum for deliberation to resolve social and cultural conflicts relevant to modern issues. This is particularly evident in the case of solving Direct Cash Assistance (BLT) and other social problems. The community’s continued trust in the legitimacy of the decisions made in the forum has made Orahua customary deliberations pivotal to modern democratic practices. This study recommends cultural transformation to preserve Orahua to address practical social challenges and problems, and has socio-economic implications for Banua (village) lives in South Nias.